PENINGKATAN KUALITAS CUSTOMER SERVICE TELKOMSEL SURABAYA DENGAN METODE SERVICE QUALITY - Benedictus Rahardjo; Septianda Angelica; Iviani Winoto; Natasah Bunardi; Elma Cathlin Tangradi (Universitas Ahmad Dahlan Indonesia, 2018)
Service companies and products are well aware of the importance of customer-centered philosophy. This paper starts from the concept of service quality and is evidenced by the gap in it. This service quality concept is an appropriate approach used to determine the difference in value between customer expectations and perceptions. The dimensions used in this paper are tangible, reliability, responsiveness, assurance, and emphaty. This paper was conducted on mobile phone provider company by reviewing customer service in this company. Respondents involved in this research are 100 customer provider who have experience on this customer service. The results that will be obtained through this research is the gap of customer service and which aspects are important according to the customer so that company can improve its services and more developed.